The Effect of Polystyrene Microplastic Exposure in the Rearing Water on Muscle Morphology of Mutiara Catfish (Clarias gariepinus Burchell, 1822) - Nurul Suwartiningsih; Aulia Fayzha Aszhara; Rani Marsela; Dian Eka Wijayanti (Postgraduate, University of Mataram, 2025)
Polystyrene (PS) is one of the most abundant microplastics in freshwater and can accumulate in fish tissues. This study investigated the effect of PS microplastic exposure in rearing water on the abundance of microplastics in muscle, and the diameter and area of myofibers in Mutiara catfish (Clarias gariepinus). A total of 120 fish were exposed to PS microplastics at concentrations of 0, 1, 10, and 100 mg/L for 28 days. Muscle samples from the right abdomen were processed using the paraffin method and stained with hematoxylin-eosin. Microplastics were extracted using 10% KOH and observed under a stereo microscope. Myofiber diameter and area were measured with Image Raster software. Data were analyzed using the Kruskal-Wallis test. Results showed significant differences among treatments (P<0.05) for all parameters. The control group had the lowest microplastic abundance and the largest myofiber size, while the highest accumulation occurred at 100 mg/L, and the smallest myofiber diameter and area were found at 10 mg/L. Exposure to PS microplastics leads to accumulation in muscle tissue and a reduction in myofiber dimensions. These findings highlight the potential adverse impacts of microplastics on fish health and underline the importance of further studies regarding ecological and human health implications.